Transforming Microbiological Diagnostics in Nosocomial Lower Respiratory Tract Infections: Innovations Shaping the Future - Ingrid G. Bustos; Lina F. Martinez-Lemus; Luis Felipe Reyes; Ignacio Martin-Loeches (Diagnostics)
Introduction: Nosocomial lower respiratory tract infections (nLRTIs), including hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP), remain significant challenges due to high mortality, morbidity, and healthcare costs. Implementing accurate and timely diagnostic strategies is pivotal for guiding optimized antimicrobial therapy and addressing the growing threat of antimicrobial resistance. Areas Covered: This review examines emerging microbiological diagnostic methods for nLRTIs. Although widely utilized, traditional culture-based techniques are hindered by prolonged processing times, limiting their clinical utility in timely decision-making. Advanced molecular tools, such as real-time PCR and multiplex PCR, allow rapid pathogen identification but are constrained by predefined panels. Metagenomic next-generation sequencing (mNGS) provides comprehensive pathogen detection and resistance profiling yet faces cost, complexity, and interpretation challenges. Non-invasive methods, including exhaled breath analysis using electronic nose (e-nose) technology, gene expression profiling, and biomarker detection, hold promise for rapid and bedside diagnostics but require further validation to establish clinical applicability. Expert Opinion: Integrating molecular, metagenomic, biomarker-associated, and traditional diagnostics is essential for overcoming limitations. Continued technological refinements and cost reductions will enable broader clinical implementation. These innovations promise to enhance diagnostic accuracy, facilitate targeted therapy, and improve patient outcomes while contributing to global efforts to mitigate antimicrobial resistance.